The contribution of ergonomics to risk analysis in the design process: the case of a future control room. - Soares, Marcelo M.; Jacobs, Karen; De la Garza, Cecilia; Labarthe, Jean-Paul; Graglia, Louis (Work)
The aim of this paper is to highlight how ergonomics contributes to risk analysis and risk management in a design project for a new reactor, the French EPR (European Pressurized Reactor). An iterative ergonomics design process has been conducted over the last 10 years through a Human Factors Engineering program at the French energy company EDF. A parallel has been drawn between a risk management process and this ergonomics process based on International Organization for Standardization (ISO) publications such as ISO/IEC Guide 73, ISO Guide 51, etc. The contribution of ergonomics to risk analysis is illustrated by an example: the automatic diagnosis, which is a very important technical device for safety. Five main types of risk have been identified via ergonomic analyses during the different design stages. Counter-measures have been implemented and their efficacy tested within the scope of new campaigns to assess human factors. However, the management of risks in such a design project requires the participation both of the different design entities involved in the project and of other experts in aspects of risk management, such as human reliability. The organization of collaborative participation remains a challenge to be addressed.